Antioxidant Activity of Gracilaria verrucosa Extract in Body Lotion Formulation - Fida Fransisca; Ahmad Shofy Mubarak; Gunanti Mahasri (Universitas Airlangga, 2026)
Indonesia has a tropical climate with high year-round solar exposure, which increases the risk of oxidative stress and premature skin aging caused by ultraviolet radiation. Red seaweed Gracilaria verrucosa is known to contain bioactive compounds with potential antioxidant properties; however, its application as a substitute for synthetic antioxidants in cosmetic formulations remains limited. This study aimed to evaluate the antioxidant activity of G. verrucosa extract and its potential as an alternative to Butylated Hydroxytoluene (BHT) in body lotion formulations. Extraction was performed using 96% ethanol through maceration for 48 hours, resulting in an extract yield of 2.47%. The study employed an experimental method with a Completely Randomized Design consisting of five treatments, including a control without antioxidants (K0), BHT 0.1%, and G. verrucosa extract at concentrations of 3%, 5%, and 7%, with four replications. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, phenolics, and steroids, while tannins were not detected. The IC₅₀ value of G. verrucosa extract was 63.57 ppm, indicating strong antioxidant activity. The IC₅₀ values of body lotion formulations were 1,266 ppm (K0), 137.77 ppm (BHT 0.1%), 175.95 ppm (EGV 3%), 131.82 ppm (EGV 5%), and 106.17 ppm (EGV 7%). The incorporation of G. verrucosa extract into body lotion exhibited antioxidant activity comparable to or higher than that of BHT 0.1%, indicating its potential as a safe and sustainable natural antioxidant for marine-based cosmetic formulations.